2016
DOI: 10.1016/j.ijheatmasstransfer.2016.02.077
|View full text |Cite
|
Sign up to set email alerts
|

Parametric study on thermal and hydraulic characteristics of laminar flow in microchannel heat sink with fan-shaped ribs on sidewalls – Part 1: Heat transfer

Abstract: In order to comprehensively assess the performance of microchannel heat sink with fan-shaped ribs on sidewalls, this third part of a three-part study focuses on the relationship between thermal resistance and pumping power, and further the entropy generation rate and performance evaluation criteria, with water and silicon used as fluid and solid for the computational domain. The microchannel has the width of 0.1 mm and depth of 0.2 mm in the constant cross-section region. The geometric parameters include the w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
29
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 118 publications
(29 citation statements)
references
References 27 publications
0
29
0
Order By: Relevance
“…To further check the accuracy and reliability of the numerical model, the numerical results of laminar flow in the microchannel have been performed by comparing with the simulation results from Chai et al as shown in Figures and . Their research was more focused on the performance of the traditional straight microchannel.…”
Section: Results and Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…To further check the accuracy and reliability of the numerical model, the numerical results of laminar flow in the microchannel have been performed by comparing with the simulation results from Chai et al as shown in Figures and . Their research was more focused on the performance of the traditional straight microchannel.…”
Section: Results and Discussionmentioning
confidence: 99%
“…Since Tuckerman and Pease first introduced the concept of liquid‐cooled microchannel enhanced heat sinks, a large number of studies were for seeking ways to improve the heat transfer efficiency of microchannel heat sinks. Many experimental and numerical studies were done to improve the performance of microchannels …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus the Reynolds number and Nusselt number values were compared with existing experimental work. The ANSYS FLUENT simulation is validated with the aid of an existing experimental work of Fan et al [22], Kalteh et al [12], and Chai et al [23]. Figure 6 shows the comparison of the present simulated work and previous experimental work.…”
Section: Validation Of Numerical Simulationmentioning
confidence: 95%
“…However in the case of triangular cavities, heat transfer enhanced due to formation of vortices in cavities and interruption of boundary-layer which significantly enhanced the convective fluid mixing. Recently Chai et al [34] performed parametric study of fan shaped ribs on side walls for Re ranging from 187-715. They considered entrance effect and viscous heating and observed 6 -101% increase in Nu and 3 -40% decrease in total thermal resistance as compared to smooth one.…”
Section: Introductionmentioning
confidence: 99%